A biosynthesis pathway for 3-hydroxypropionic acid production in genetically engineered Saccharomyces cerevisiae. Issue 12 (28th May 2021) - Tong, Tian; Tao, Zhenyan; Chen, Xiulai; Gao, Cong; Liu, Hui; Wang, Xiaoling; Liu, Gao-Qiang; Liu, Liming
Abstract : The oxaloacetate pathway using glucose as a substrate was developed to synthesize 3-HP. The intracellular ATP supply was enhanced to optimize the 3-HP production through a dephosphorylation regulation strategy. Abstract : 3-Hydroxypropionic acid (3-HP) is an emerging platform chemical, which can be used for the production of various value-added chemicals. The traditional chemical synthesis of 3-HP has some difficulties in meeting the new sustainable development goals. Accordingly, microbial cell factories offer a green and sustainable method for the biosynthesis of 3-HP. Herein, a novel oxaloacetate pathway was successfully established for 3-HP biosynthesis. Firstly, a 3-HP production module was designed and constructed in Saccharomyces cerevisiae by overexpressing pyruvate carboxylase, benzoylformate decarboxylase, and 3-hydroxyisobutyrate dehydrogenase. Secondly, promoter engineering was used to optimize the glc7 expression, which could regulate the dephosphorylation of hexokinase to enhance the cytoplasmic energy metabolism, resulting in a 74.4% increase in 3-HP titer. Furthermore, a quorum-sensing system was applied to regulate the ptc7 expression, which could control the dephosphorylation of citrate synthase and mitochondrial hydroxylase to enhance the mitochondrial energy metabolism, resulting in a 98.0% increase in 3-HP titer. Finally, to further improve the 3-HP production, dynamic control of dephosphorylation was achieved to optimize the cytoplasmic and mitochondrial energy metabolism, resulting in a 4.2-fold increase in 3-HP titer in a 5 L bioreactor. The final engineered strain, thTAM-47, produced 18.1 g L −1 3-HP, which is the highest level of 3-HP production in S. cerevisiae to date. This work showed the shortest pathway for 3-HP production using glucose as a substrate in S. cerevisiae at present. Also, this is the first report on improving the pathway efficiency of 3-HP biosynthesis using a dephosphorylation regulation strategy to increase the intracellular ATP level.